The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/3483511
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Nanoemulsion from Ethanolic Extract of Centella asiatica (NanoSECA) Using D-Optimal Mixture Design to Improve Blood-Brain Barrier Permeability

Abstract: The evidence on the neuroprotective impact of Centella asiatica (C. asiatica) has been greatly documented in recent years. However, a major obstacle that remains to be overcome is the capacity of the active molecules in C. asiatica to cross the blood-brain barrier (BBB). In this study, we explored the possibilities of using a D-optimal mixture design to fabricate nanoemulsion of C. asiatica (NanoSECA) for better brain bioavailability. The parameters for optimization were the percentage of water (10–80% w/v) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
(77 reference statements)
1
7
1
Order By: Relevance
“…Comparatively, the mean particle sizes of xanthone and anthocyanin nanoemulsions prepared in our study were smaller than those reported by Jusril [ 36 ] and Bamba et al [ 37 ], with the former using coconut oil, Tween 80, Span 80, and ethyl acetate extract from mangosteen peel to prepare a xanthone nanoemulsion with the mean particle size at 181 nm, and the latter using corn oil, polyglycerol polyricinoleate, and ethanol extract from blueberry pomace to prepare a water-in-oil-in-water anthocyanin nanoemulsion with the mean particle size at 400 nm. Obviously, the difference in mean particle size of the nanoemulsion can be attributed to the variation in oil, surfactant and solvent varieties as well as the extraction method.…”
Section: Resultscontrasting
confidence: 92%
“…Comparatively, the mean particle sizes of xanthone and anthocyanin nanoemulsions prepared in our study were smaller than those reported by Jusril [ 36 ] and Bamba et al [ 37 ], with the former using coconut oil, Tween 80, Span 80, and ethyl acetate extract from mangosteen peel to prepare a xanthone nanoemulsion with the mean particle size at 181 nm, and the latter using corn oil, polyglycerol polyricinoleate, and ethanol extract from blueberry pomace to prepare a water-in-oil-in-water anthocyanin nanoemulsion with the mean particle size at 400 nm. Obviously, the difference in mean particle size of the nanoemulsion can be attributed to the variation in oil, surfactant and solvent varieties as well as the extraction method.…”
Section: Resultscontrasting
confidence: 92%
“…346 Advanced nanotechnological approaches, such as stimulus-responsive or smart delivery systems, may enable the on-demand release of AC, responding to specific cues present in the wound microenvironment for precise and timely therapeutic interventions. 347 Moreover, the incorporation of innovative biomaterials and bioengineering techniques may facilitate the development of multifunctional scaffolds or dressings capable of simultaneously providing structural support, promoting tissue regeneration, and delivering AC in a controlled manner. 348 Additionally, combining AC with other bioactive agents or growth factors within nanocarriers could potentially create synergistic therapeutic effects, accelerating wound closure, reducing inflammation, and minimizing scar formation.…”
Section: Future Prospectivementioning
confidence: 99%
“…The PDI is a valuable parameter to evaluate the stability of the nanoemulgel formulation, representing the distribution of a population's size within a given sample [48]. Since all LN formulations presented a PDI value lower than 0.5, it indicates a narrow and uniform particle size distribution within all samples [49]. On the other hand, the zeta potential is a relevant factor to assess the stability of nanosuspensions.…”
Section: Ln Formulations' Particle Size Polydispersity Index Zeta Pot...mentioning
confidence: 99%